Dissolved nutrient exports from natural and human‐impacted Neotropical catchments. Issue 4 (14th January 2016) - Gücker, Björn; Silva, Ricky C. S.; Graeber, Daniel; Monteiro, José A. F.; Brookshire, E. N. Jack; Chaves, Ronaldo C.; Boëchat, Iola G.
Abstract: Aim: Neotropical biomes are highly threatened by land‐use changes, but the catchment‐wide biogeochemical effects are poorly understood. Here, we aim to compare exports of dissolved nitrogen (N) and phosphorus (P) from natural and human‐impacted catchments in the Neotropics. Location: Neotropics. Methods: We measured streamwater nutrient concentrations and exports in 20 south‐eastern Brazilian catchments with different land uses (natural Cerrado/semi‐deciduous forest, pasture, intensive agriculture and urban areas) and conducted a meta‐analysis on nutrient exports from Neotropical catchments, both natural and human‐impacted. Results: Organic forms dominated dissolved nutrient exports in central/south‐east Brazil in both natural and human‐dominated catchments. Our meta‐analysis suggests that there is wide geographic variability in the natural dominance of organic versus inorganic nutrient exports across the Neotropics, and for N a tendency for inorganic and organic forms to vary inversely across sites. We found strong land‐use effects, especially in urban areas. In areas naturally dominated by organic N exports, land use did not overturn that dominance, but rather increased the concentration of both inorganic and organic N. In catchments dominated by inorganic N exports or showing equivalent organic and inorganic exports, land use also caused organic exports to be dominant. Land‐use effects on P were unclear, probably owing to a paucity of available data, but our results from south‐east Brazil suggested that land use also increases dissolved P exports. Main conclusions: We show that dominance of inorganic versus organic nutrient exports is highly variable across natural Neotropical catchments, a pattern contrasting with the general tendency for dominance of organic N in natural temperate catchments. Further, we found a general dominance of organic N in most human‐impacted catchments, which is in contrast to strong dominance of inorganic N in most human‐impacted temperate catchments. Finally, we find that urbanization exerts the strongest impacts on nutrient exports, thus underscoring wastewater treatment as a critical management priority under future land‐use change.